HUBUNGAN ANTARA METODE HANIFIDA DENGAN MOTIVASI MENGHAPAL AL-QUR’AN PADA SISWA - Kartiwa, Iwa; Pasya, Rayi; Rahmanwangsih, Yuli Altri (Jurnal Penelitian Pendidikan Islam, 2015)
This research was conducted to explore and analyze the relationship between methods with motivation to memorize students. After the analysis of the data obtained can be concluded as follows: 1) The application of the Hanifida method in memorizing the Koran in class VII of SMP Negeri 4 Ciamis was done very well; 2) Motivation to memorize the Koran of students before following the application of the Hanifida method is quite good category because the quality of the assessment is 3.12 which is located at intervals between 2.5 - 3.5. Motivation to memorize the Koran of students after following the application of the Hanifida method is high because the quality of the assessment is 3.99 which is found at intervals between 3.5 - 4.5; 3) Between the application of the Hanifida method with the motivation to memorize the Koran students there is a significant relationship. This is evident from the results of the calculation of the correlation coefficient between the two variables 0.59 in the interval 0.40 - 0.59. Because Fcount is 4.337 greater than the Ftable value which is 1.216, reject Ho.